Metode Pembelajaran Observasi Lapangan (Outdoor Study) Sebagai Konsep Pembelajaran Buku Ajar Interior Bangunan Komersial - Agustin, Dyan (Universitas Medan Area, 2024)
Commercial Building Interior is one of the elective courses in the Architecture study programme that discusses aesthetic principles in commercial building interiors including offices, shops/retail, lodging facilities, cultural and entertainment facilities and so on. This research aims to analyse the effectiveness of the outdoor study learning method on students' understanding of the concept of commercial building interior design. Through qualitative and quantitative research, it is found that the field observation method contributes significantly in improving students' ability to analyse space, identify the latest design trends, and develop creativity in designing interior design concepts. This article will present the complete research results, including data analysis and discussion of implications for interior design curriculum development.